Factors affecting the decline in sales of palm oil at RISDA Melaka for the January-June 2010 / Khadijah Hashim - Hashim, Khadijah (Faculty of Business and Management, 2010)
The important things that company should know when they want to achieve higher sales is to know what are the factors affecting the decline in sales. For RISDA, they should know what are actually the factors affecting the decline in sales of palm oil based on the study done. Other than that, they should know how to solve the problem when their sales are decline and affect the income for the company. This research articles evaluate on what are the factors that contribute to the decline in sales of palm oil at RISDA Melaka for January-June 2010 and RISDA should aware with the findings. Even though the findings show that only 2 months the sales are decline, but they should take corrective action to make sure the decline in sales will not happen again in the future. After reviewing related literature the data from that literature has been summarized and is used to get the gap between the company used and the practice in the assessment to make the sales increase in the future and company will find the solution for their problems. The data of sales of palm oil have been collected from January until June 2010 to analyze on the trend of sales of palm oil at RISDA Melaka. From the data, it shows the relevant solution that RISDA can do to increase their sales of palm oil.